Meningkatkan Pemahaman Siswa pada Mata Pelajaran Komputer dan Jaringan Dasar Menggunakan Modul Digital Interaktif - Renaldo Hadji; Arip Mulyanto; Manda Rohandi; Arif Dwinanto (Universitas Negeri Gorontalo, 2023)
Basic Computers and Networks is a productive subjects of the Software Engineering expertise program at SMK Negeri 3 Gorontalo. However, in the policy of implementing online learning, there are several problems, including the learning media is deemed unattractive so that students quickly feel bored in the learning process, the learning media also does not involve students actively so that learning is still teacher-centered, and student have grades that do no meet the Minimum Completeness Criteria (KKM) which mean students’ understanding of the material is still low. This study aims to know the level students’ understanding of basic computer and network subject after an interactive digital module . This is a pre-experimental study using a One-Group Pretest-Posttest Design. The fiding shows that there is an improvement in students‘ understanding after using the interactive digital module. It is based on of difference in the average value of the pretest and posttest obtained by 0.00 which is smaller than 0.05. Thus, it is concluded that learning using an interactive digital module in Computer and Basic Network subject can improve students’ understanding of the subject material.Keywords: interactive digital module; students’ understanding; pre-experimental